Análise socioambiental da Serra do Cabral, Simão Dias-SE: proposição do uso de tecnologias digitais para o ensino das Ciências Ambientais - Amorim, Jamile Santos (2022)
The socio-environmental problems are increasingly evident, the ways of appropriation of environments must be questioned in view of the view that natural areas are constantly being degraded, especially in the face of the constant growth of cities. In this sense, this research analyzes the perception of existing socio-environmental problems from the implementation of a tourist spot in a previously natural area, popularly known as "Serra do Cabral", located in the municipality of Simão Dias/SE. Its main objective is: To develop critical EE strategies for the tourist development of Serra do Cabral, in Simão Dias - SE, in addition to identifying the current socio-environmental impacts existing in the area; highlight the changes that took place in the Serra during and after the urbanization process; and later to develop a didactic/technological product through the natural scenarios of the municipality. Thus, it is considered an efficient and attractive way to create an environmental sensitivity in the target audience of the project and in the population in general. Of an exploratory/explanatory nature, to carry out this research, contact was made with the participants, the local community to obtain data through field action research: in loco observation, semi-structured interviews, conversation circles and photographic records. From the methodology applied, it was possible to understand the process of removal of the population in relation to the Serra do Cabral, and that in the face of all the existing problems the technical product will be an important tool for sharing specific information of the study area and the municipality as a brings together individuals with existing problems around them.